EXPERIENCE OF THE EFFICIENT USING OF METHOTREXATE FOR SUBCUTANEOUS ADMINISTRATION IN PATIENT WITH POLYARTICULAR JUVENILE IDIOPATHIC ARTHRITIS - S. A. Ushakova (Voprosy Sovremennoj Pediatrii, 2014)
The article describes successful case of the methotrexate monotherapy through subcutaneous administration (15 mg/m2 of body surface per week) for treatment of the polyarticular juvenile idiopathic arthritis in the girl in the age of 4. After 6 and 12 months of the methotrexate therapy the significant reduction of the clinical and laboratory disease activity indices and increase in functional activity of the child according to the pediatric ACR criteria for 50 and 90% respectively were observed. No adverse experience during the monotherapy was recorded. Development of inactive disease phase after 15 months of treatment allows predicting the development of pharmacological remission in patient in the prospective. Timely (immediately after the disease was diagnosed) administration of methotrexate allowed preventing the disablement of the child and improving the life quality of both the patient and her family.